2013
DOI: 10.1007/s40265-013-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Ramucirumab (IMC-1121B) for Cancer Treatment: From Benchside to Clinical Use

Abstract: Although antiangiogenic treatments have produced milestone advances in the treatment of several diseases, and have significantly extended the median survival of cancer patients, these agents share some weaknesses, including a limited impact on the overall cure rate, a fleeting effect because of redundant pathways or early appearance of resistance mechanisms, and the lack of predictive factors for treatment selection. Recent data suggest that antibodies targeting the vascular endothelial growth factor axis exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…In the phase III RAINBOW trial, the addition of ramucirumab significantly improved OS from 7.36 months to 9.63 months (HR: 0.807; 95% CI: 0.678-0.962; p 5 .0169) [30]. Ramucirumab has shown varying degrees of efficacy in renal, uterine, colorectal, and ovarian carcinoma [31,32]. Most recently, results of ramucirumab trials in NSCLC and breast cancer have been reported.…”
Section: Afliberceptmentioning
confidence: 99%
“…In the phase III RAINBOW trial, the addition of ramucirumab significantly improved OS from 7.36 months to 9.63 months (HR: 0.807; 95% CI: 0.678-0.962; p 5 .0169) [30]. Ramucirumab has shown varying degrees of efficacy in renal, uterine, colorectal, and ovarian carcinoma [31,32]. Most recently, results of ramucirumab trials in NSCLC and breast cancer have been reported.…”
Section: Afliberceptmentioning
confidence: 99%
“…A VEGFR-2-ligand-kö-tődés következményeként a sejten belül több jelátviteli út aktiválódik és ennek következtében fokozódik a tumorangiogenezis [3]. Annak ellenére, hogy a VEGF-A receptorkötő affinitása a VEGFR-2-receptorhoz csak tizede a VEGFR-1-hez mutatott aktivitásnak, mégis a VEGFR-2-t tekintik a tumor-angiogenezis főszereplőjé-nek, mivel a foszforilációja által elindított intracelluláris jelátviteli kaszkád hatékonyabb intermediereket aktivál, mint a másik két receptor [4]. A VEGF-ellenes terápiák az onkológiai gyógyszerfejlesztések élvonalába kerültek [5].…”
Section: A Gyógyszer éS Hatásmechanizmusaunclassified
“…Among many novel antiangiogenic drugs, ramucirumab, a fully human IgG 1 monoclonal antibody specifically directed against VEGFR-2, is emerging as a new therapeutic option [67]. The phase III, placebo-controlled, double-blinded REGARD trial was conducted with the aim of evaluating the safety and efficacy of ramucirumab as second-line treatment in 355 patients with advanced, unresectable gastric or GEJ cancers.…”
Section: Targeting Vegfr-2: the Example Of Ramucirumabmentioning
confidence: 99%